The functional and anatomical dissection of somatosensory subpopulations using mouse genetics - Le Pichon, Claire E.; Chesler, Alexander T. (Frontiers in Neuroanatomy, 2014)
The word somatosensation comes from joining the Greek word for body (soma) with a word for perception (sensation). Somatosensory neurons comprise the largest sensory system in mammals and have nerve endings coursing throughout the skin, viscera, muscle, and bone. Their cell bodies reside in a chain of ganglia adjacent to the dorsal spinal cord (the dorsal root ganglia) and at the base of the skull (the trigeminal ganglia). While the neuronal cell bodies are intermingled within the ganglia, the somatosensory system is in reality composed of numerous sub-systems, each specialized to detect distinct stimuli, such as temperature and touch. Historically, somatosensory neurons have been classified using a diverse host of anatomical and physiological parameters, such as the size of the cell body, degree of myelination, histological labeling with markers, specialization of the nerve endings, projection patterns in the spinal cord and brainstem, receptive tuning, and conduction velocity of their action potentials. While useful, the picture that emerged was one of heterogeneity, with many markers at least partially overlapping. More recently, by capitalizing on advances in molecular techniques, researchers have identified specific ion channels and sensory receptors expressed in subsets of sensory neurons. These studies have proved invaluable as they allow genetic access to small subsets of neurons for further molecular dissection. Data being generated from transgenic mice favor the model whereby an array of dedicated neurons is responsible for selectively encoding different modalities. Here we review the current knowledge of the different sensory neuron subtypes in the mouse, the markers used to study them, and the neurogenetic strategies used to define their anatomical projections and functional roles.